Unlocking Institutional Capacity for Sustainable E-Government Transformation - Wahid, Muhammad; Rahman, Siraju; Muhammad Yusuf; Busyairi, Muhammad Hasan (Sinergi International Journal of Communication Sciences, 2024)
This paper examines systemic factors influencing digital transformation in the public sector, with a focus on bureaucratic structures, regulatory environments, and human resource capabilities. The study aims to explore how strategic alignment and collaborative leadership shape the success of digital initiatives. Utilizing a narrative review approach, the analysis synthesizes evidence from global case studies and recent empirical research. The findings indicate that while technological adoption improves operational efficiency, systemic constraints often hinder transformative outcomes. Leadership vision, stakeholder prioritization, and inclusive strategies are identified as pivotal in addressing challenges such as legacy system integration, uneven infrastructure, and resistance to change. The discussion highlights significant disparities between central and local agencies, underscoring the need for adaptive policy frameworks, standardized digital maturity models, and strengthened cross-sector collaboration.This study emphasizes the necessity of holistic digital strategies that merge technological innovation with institutional reform. The implications suggest that targeted policy measures—such as interoperable system development, capacity-building programs, and GovTech ecosystem support—are crucial for long-term digital governance success. Future research should delve into context-specific digital readiness and performance frameworks to bridge current knowledge gaps and support inclusive digital transformation pathways.